GROUNDWATER GEOCHEMISTRY OF RROGOZHINA AQUIFER (WESTERN ALBANIA) - Luzati, S.; Beqiraj, A.; Jaupaj, O. (Bulletin of the Geological Society of Greece, 2016)
This paper aims to make a geochemical characterization of the groundwater of Rrogozhina aquifer which extends over the Albanian pre-Adriatic depression covering a surface of 2100 km2. It is a multilayered aquifer consisting of intercalations between water-bearing Pliocene sandstone and conglomerate with impermeable clay layers. This aquifer occurs under typically artesian conditions because of its impermeable clay basement and semi-impermeable Quaternary cover. The groundwater shows variable geochemical composition due to different mineralogical composition of its medium and vast extension of the aquifer. However, the mainly magmatic - carbonatic mineralogical composition of the water - bearing sandstones and conglomerates has determined a geochemical composition of groundwater consisting mostly of HCO3-Mg-Ca hydrochemical groundwater type. Dissolution of minerals seems to be the major geochemical processes in the formation of the groundwater composition. The above mainly magmatic composition of sandstones and conglomerates is also responsable for the high content of iron in the grounwater of this aquifer. Iron content is higher in sandstone related groundwater where the silt fraction is mainly composed by ironbearing minerals such as magnetite, epidote, granate, sphene, amphibole and pyroxene. The general mineralization and general hardness of groundwater range from 500 to 800 mg/l and from 11 to 25ºdH, respectively.